KEMAMPUAN MENULIS CERITA PENDEK BERDASARKAN UNSUR INTRINSIK DENGAN MENGGUNAKAN MEDIA GAMBAR OLEH SISWA KELAS XI SMK NEGERI 6 KUPANG - Margaretha Dulce Da Costa Tokan; Semuel H. Nitbani; Margareta P. E. Djokaho (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The focus of this study is to examine the ability of eleventh-grade students of SMK Negeri 6 Kupang to write short stories based on intrinsic elements using picture media. The purpose of this research is to describe students’ ability to write short stories based on intrinsic elements through the use of picture media among eleventh-grade students of SMK Negeri 6 Kupang. Picture media were used by the researcher to attract students’ interest and serve as visual media to stimulate students’ thinking in developing ideas or concepts that would be expressed in the form of short story texts. The method employed in this study is a qualitative descriptive method. The theory applied in this research is writing theory. Based on the results of data analysis on students’ ability to write short stories based on intrinsic elements using picture media among eleventh-grade students of SMK Negeri 6 Kupang, out of 33 students studied, 3 students (9.09%) were categorized as very good in writing short stories, 6 students (18.18%) were categorized as good, 18 students (54.54%) were categorized as fair, and 6 students (18.18%) were categorized as poor in writing short stories. Based on the scores obtained, it can be concluded that the average score of the eleventh-grade students of XI PPLG 1 at SMK Negeri 6 Kupang is 77.63. This indicates that some students are able to produce very good short stories, while others have not yet been able to produce good short stories. These findings show that the short story writing ability of the eleventh-grade students of XI PPLG 1 at SMK Negeri 6 Kupang, in accordance with intrinsic elements and the linguistic rules of short stories, has met the Minimum Mastery Criteria (KKM) of 75.